Breakfast of champions - Vonnegut, Kurt . (Dell publishing, 1973)
In a frolic of cartoon and comic outbursts against rule and reason, a miraculous weaving of science fiction, memoir, parable, fairy tale and farce, Kurt Vonnegut attacks the whole spectrum of American society, releasing some of his best-loved literary creations on the scene.